2017
DOI: 10.3390/molecules22122133
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Catalytic Property of the Glycoside Hydrolase LXYL-P1–2 by Directed Evolution

Abstract: The glycoside hydrolase LXYL-P1–2 from Lentinula edodes can specifically hydrolyze 7-β-xylosyltaxanes to form 7-β-hydroxyltaxanes for the semi-synthesis of paclitaxel. In order to improve the catalytic properties of the enzyme, we performed error-prone PCR to construct the random mutant library of LXYL-P1–2 and used the methanol-induced plate method to screen the mutants with improved catalytic properties. Two variants, LXYL-P1–2-EP1 (EP1, S91D mutation) and LXYL-P1–2-EP2 (EP2, T368E mutation), were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Moreover, the activities of the purified enzymes were measured through hydrolysis of the chromogenic substrates PNP-Xyl and PNP-Glu, respectively 30 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the activities of the purified enzymes were measured through hydrolysis of the chromogenic substrates PNP-Xyl and PNP-Glu, respectively 30 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the resultant strains ( Fig. 5 A) were further cultivated for 7 days prior to the determination of the volumetric and biomass enzyme ( β -xylosidase) activities described previously 30 . The results indicated that, except for UPC, both PDI and VHB could apparently enhance the volumetric and biomass enzyme activities compared with those of control; typically, VHB had exerted the highest effect on day 7 ( Figure 5 , Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the effect of I368E mutation on the enzyme activity, the recombinant yeast GS115-3.5K-P1−1 I368E was constructed, and its volumetric and biomass enzyme activities were detected as described previously [32]. After induction by methanol for 4 days, the enzyme activities of GS115-3.5K-P1−1 I368E had exceeded those of GS115-3.5K-P1−1 (Figure 1).…”
Section: Resultsmentioning
confidence: 97%
“…In our previous study, the directed evolution of LXYL-P1−2 had been conducted. From the random mutant library created by error-prone PCR, we obtained a mutant LXYL-P1−2-EP2 (LXYL-P1−2 T368E ) that harbored the T368E mutation, which exhibited a 47% increase in its catalytic efficiency on XDT and elevated stability in the range of pH ≥ 6 compared with LXYL-P1−2 [32]. Recently, we found that the mutant LXYL-P1−1 I368T also exhibited similar β-xylosidase and β-glucosidase activities compared with the high-active LXYL-P1−2, although the activities were lower than those of LXYL-P1−1 A72T , LXYL-P1−1 V91S (the most active single mutant), and the double mutant LXYL-P1−1 A72T /V91S [33].…”
Section: Introductionmentioning
confidence: 99%